Significant correlations of upregulated MPO expression with cytokine imbalance in ankylosing spondylitis patients and the inhibitory effect mediated by mesenchymal stem cells - Shubei Liu; Chunjuan Yang; Donghua Xu; Bingjie Gu; Minning Shen (BMC Musculoskeletal Disorders)
Abstract Background Little is known regarding both the role of myeloperoxidase (MPO) and the impact of mesenchymal stem cells (MSCs) on inflammatory and immune responses in ankylosing spondylitis (AS). This study is aimed to explore the role of MPO and the regulatory effect of umbilical cord-derived MSCs on MPO expression in monocytes in AS. Methods MPO mRNA expression in the peripheral blood mononuclear cells (PBMCs) was detected by Real-time PCR. Cytokines including IL-2, IFN-γ, IL-17 A, IL-4, IL-10, IL-6 and TNF-α were determined by flow cytometry. A co-culture system was established by culturing THP-1 cells with MSCs at a ratio of 5:1. Results Increased mRNA expression of MPO was observed in PBMCs of AS patients compared to healthy controls (P < 0.05). The mRNA expression of MPO was positively associated with C-reactive protein (CRP) and erythrocyte sedimentation rate (ESR) (P < 0.05) in AS. Besides, the levels of IL-2, IL-10, IFN-γ, IL-17 A, IL-4, IL-6, TNF-α in plasma were notably increased in AS (P < 0.05). Positive correlations between MPO expression and IL-2, IFN -γ, IL-4, TNF-α as well as IL-6 were demonstrated in AS (P < 0.05). Furthermore, MSCs remarkably suppressed the mRNA expression of MPO along with the secretion of IL-17 A and TNF-α, but promoted IL-10 generation in monocytes. Conclusion MPO expression is significantly upregulated and correlates with cytokine imbalance in AS. It may serve as a valuable immunotherapeutic target for AS. MSCs can significantly inhibit monocyte-mediated inflammatory response potentially by downregulating MPO in monocytes.